Case study research : design and methods - Yin, Robert K. 4 0 16; 5 (Los Angeles, California : Sage Publications, 2009)
Discussess how to apply case study research to practice, covering quantitative analysis, mixed methods research designs, methodological insights, collection of evidence, reporting, and more.
Includes bibliographical references and indexes.
Professional.;Adult.
Keywords: 2 -- 0; 6; Research;Methodology. -- Case method.;Social sciences -- 20; 20; 2